Allium - Lysenkova Wiklander, Mariya (SciLifeLab Serve, 2026)
ALLIUM (ALL subtype Identification Using Machine learning) is a multimodal classifier of molecular subtypes in pediatric acute lymphoblastic leukemia, using DNA methylation (DNAm) and gene expression (GEX) data